2021
DOI: 10.1002/lio2.572
|View full text |Cite
|
Sign up to set email alerts
|

Flexible fiber‐based CO2 laser vs monopolar cautery for resection of oral cavity lesions: A single center randomized controlled trial assessing pain and quality of life following surgery

Abstract: Importance This study reports the impact of laser surgery on quality of life in patients with oral cavity lesions. Objective To compare postoperative pain and quality of life in patients treated with flexible fiberoptic CO2 laser vs electrocautery in patients with oral cavity precancerous lesions and early stage cancers. Design Randomized controlled trial. Setting Single center. Participants Patients with premalignant oral cavity lesions and early stage oral cancer. Intervention Patients were randomized to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Although four studies had not defined the type of laser used, other studies reported the outcomes with CO 2 laser, 14,15,23 Nd:YAG laser, 19 Er:YAG laser, 18 and the diode laser 17 . Within the 10 papers reviewed, among the various QoL assessment tools utilized for the evaluations, the most commonly used instrument was version 4 of the UW‐QOL 14–16,20 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although four studies had not defined the type of laser used, other studies reported the outcomes with CO 2 laser, 14,15,23 Nd:YAG laser, 19 Er:YAG laser, 18 and the diode laser 17 . Within the 10 papers reviewed, among the various QoL assessment tools utilized for the evaluations, the most commonly used instrument was version 4 of the UW‐QOL 14–16,20 …”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 90% were from Europe that had been conducted in three different European countries (Table 1 ). Five of the 10 studies were conducted in the United Kingdom, three in Italy, and one each in the United States 15 and Turkey. 17 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations